O significado da autoestima de mulheres idosas que vivem no rural - Silva, Pâmela Giuli Fleck da (2024)
Brazil is experiencing the age of aging, where in recent years there has been a large increase in the elderly population. The aging process is experienced uniquely by each individual, and depending on how it is experienced, this cycle of self-esteem is altered, especially in females due to the pressure and standards set for women. Likewise, the rural context is a determinant that influences the process of living and the self-esteem of elderly women who live in this environment. Thus, the objective of the present study is to understand the meaning of selfesteem in elderly women living in a rural context. This is a study with a qualitative research method, based on Grounded Theory (TF). The study was developed with 23 elderly women living in a rural context, from January to March 2024. The study location was a Rural ESF in a municipality in the Northwest of the State of Rio Grande do Sul. Data collection was carried out by through an individual open interview, with a questionnaire with seven previously constructed guiding questions. The data was analyzed using the guiding aspect of Charmaz's TFD. Rigorous research into the ethical aspects established by Resolution 466/2012. From the collection and analysis of the data obtained, there were 6 categories and 15 subcategories. Through this study it was possible to understand the self-esteem of rural elderly women and the factors that influence this. Study participants revealed that social and family relationships, health, physical activity, autonomy, self-care, religion and grief can influence self-esteem in a positive or negative way, depending on the life cycle and experience. In short, it is concluded that carrying out this study increases the visibility of women who live in rural contexts, allowing them to understand the importance of self-esteem, the challenges and strategies to promote selfesteem. Such discoveries provide the opportunity for the implementation of best practices for the health and well-being of elderly women living in rural contexts.